Public Reason in Times of Corona: Countering Disinformation in the Netherlands - Buijsen, Martin (Cambridge quarterly of healthcare ethics, 2025)
Who should decide what passes for disinformation in a liberal democracy? During the COVID-19 pandemic, a committee set up by the Dutch Ministry of Health was actively blocking disinformation. The committee comprised civil servants, communication experts, public health experts, and representatives of commercial online platforms such as Facebook, Twitter, and LinkedIn. To a large extent, vaccine hesitancy was attributed to disinformation, defined as misinformation (or data misinterpreted) with harmful intent. In this study, the question is answered by reflecting on what is needed for us to honor public reason: reasonableness, the willingness to engage in public discourse properly, and trust in the institutions of liberal democracy.